„Der er gået politik i børnesygdomme“. MFR-vaccinationens indførelse i Danmark ca. 1983-1987 - Berg, Anne Hagen (Historisk Tidsskrift, 2021)
Politicizing childhood diseases. The introduction of MMR vaccinations in Denmark 1983-1987 In 1987, after a multi-year policymaking process, Denmark introduced the combined measles-mumps-rubella (MMR) vaccine into the childhood vaccination program. Using the multiple streams framework developed by John Kingdon, this article traces how MMR was placed on the political agenda and eventually introduced on a national scale. During the 1960s, 1970s and 1980s, most Western countries had introduced vaccines against one or more of the diseases. By contrast, the Danish health authorities considered measles and mumps trivial childhood diseases, and congenital rubella syndrome was solved by offering abortions to pregnant women who were infected. Thus, the first step in the political process was the reframing of all three diseases as serious health threats, a task made easier by pressure placed by the World Health Organization on Denmark to contribute to its global campaign against measles. Once urgency was established, medical data was presented to demonstrate the value of providing all three vaccines in a single inoculation In 1983, the National Board of Health issued a recommendation for an MMR vaccination program aimed at children ages 15 months and 12 years. The Ministry for the Interior welcomed the recommendation, but the tight budgets and the Conservative-led government made it difficult to find money for the new vaccines. While the ministry deployed different strategies, among others a cost-benefit-analysis, it failed to convince the government as a whole. In the end, other actors played a decisive role. County-level officials had been convinced by the cost-benefit analysis, so in late 1985, the Association of County Councils initiated a MMR program. Shortly thereafter, the Danish Social Liberal Party (Radikale Venstre) proposed a parliamentary resolution in favour of the introduction of MMR. This, in combination with pressure from parents and the media, forced the government to introduce MMR. Hence, the article concludes, the introduction of MMR in Denmark was delayed due to political and financial circumstances in the 1970’s and 1980’s, and the eventual introduction was due to four circumstances: 1) a change in the health authority perceptions of the diseases; 2) public health and prevention became a political priority as a result of the tight state budgets; 3) pressure from WHO, and 4) pressure from the public, the counties and the Parliamentary opposition.